Message Sculptor untuk Relawan SAPA Keluarga: Penguatan Pengetahuan dan Komunikasi Kebijakan Partisipatif di Tingkat Kelurahan - Rina Herlina Haryanti; Ismi Dwi Astuti Nurhaeni; Sajida Sajida; Sri Yuliani; Asal Wahyuni Erlin Mulyadi; Zuleyka Alifa Fikriya (Faedah: Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
The Women-Friendly, Child-Caring, and Quality Family Urban Village Program in Surakarta City positions Sahabat Perempuan, Anak, dan Keluarga (SAPA Keluarga) volunteers as a link between government programs and residents. Initial identification during the activity showed that the volunteers still experienced difficulties in understanding their mandate, success indicators, and how to formulate messages appropriate to their target audiences. This community service activity aimed to strengthen the volunteers' knowledge and initial policy communication capacity through the Message Sculptor approach combined with participatory game cards. The program involved 50 volunteers from Serengan and Danukusuman Urban Villages and was implemented through four stages: understanding, unlearning, unconference, and upshifting. The evaluation used aggregate score records before and after the activity, process observation, group discussions, and participant reflections. The mean knowledge score increased from 43.50 (SD = 7.02) to 79.20 (SD = 6.82), with a mean difference of 35.70 points. During facilitated exercises, participants began to formulate messages based on audience, values, objectives, emotions, and communication media, and to develop an initial SAPA Keluarga Division Action Plan (RAD-SAPA). These findings describe immediate changes within the training context and are not used to infer causal relationships, long-term behavioral change, or institutional sustainability. Message Sculptor may be considered a participatory learning tool to help volunteers translate program content into more contextual messages, supported by mentoring, role clarity, and organizational coordination.